Childhood nasal obstruction and sleep-disordered breathing during clinical setting: Myth or reality? - Zaffanello, Marco; Lippi, Giuseppe; Tenero, Laura; Piazza, Michele; Sacchetto, Luca; Nosetti, Luana; Gasperi, Emma; Piacentini, Giorgio (The European Research Journal, 2019)
Objectives: The severity of sleep apneas largely depends on abnormal size of upper airway. Therefore, nasal examination is essential part of clinical evaluation of children with sleep-disordered breathing. Methods: We performed a retrospective survey involving children aged 4 years and older which underwent in-laboratory overnight cardiorespiratory polygraph study between January 2016 and May 2017. Nasal obstruction test was used to score severity. Results: Fifty-three children (62% males) with a median age of 6.1 (IQR 3.1) years were enrolled in this study. Linear regression analysis showed that nasal obstruction score was correlated with apnea-hypopnea index (β=0.345; p < 0.014) and oxygen desaturation index (β=0.328; p < 0.022), whilst no association was found with age, BMI Z-score, snoring and phase angle. Correlation analysis also showed that nasal obstruction score was correlated with apnea-hypopnea index (r=0.364; p = 0.009) and oxygen desaturation index (r=0.350; p = 0.012) after adjustment for age and BMI Z-score., but not with snoring time or phase angle degree. Conclusions: Nasal obstruction test may be a useful, time saving assessment which aid exploring sleep disordered breathing in children. However, this test should not be used alone because it is plagued by objective consideration and at risk of under or overestimation.